Mediação pedagógica em ambientes virtuais de aprendizagem - Rigo, Rosa Maria (2014)
This study presents a research with descriptive exploratory approach, which analysis was qualitative, from a study that approached the pedagogic mediation in virtual learning environments. The analysis and thoughts came from the various authors works that approach the theme, focusing in to discuss the relevant aspects of pedagogic mediation, associate to technologies on the didactics processes mediation in learning virtual environments. We used as searching instruments an online questionnaire, applied to 17 teachers of public schools which work with preschool and elementary school of different regions of Brazil and outside. Those teachers were located in two lists from different extension activities and continuous formation that happened before than this dissertation. The study object questioning was about: Which online pedagogic mediation strategies contribute more for the teaching and learning virtual processes? The guiding questions stablished to the investigation were the following: Which are the online pedagogic practices that benefit more the online pedagogic mediation on the searching subjects? Which are the indicators to the qualification of practice of online pedagogic mediation from what was found on the research? As results of this search we can point that the strategies of online pedagogic mediations that more contribute to the virtual teaching and learning processes are the mediation which incentive the sharing of knowledge, the mediations that include interactivity, the mediations that include collaborative activities, the ones that offered feedbacks in short period of time, the ones that include conditions for execution of required activities, also the ones that give the belong feeling, what means, those that are possible for the group share/develop critical/constructive thoughts about their own knowledge, (re)balancing, that is to say, different views to the same problem, offering new constructions and (re)constructions. Those results represent a current scenario of new contexts of learning that deserve to be evaluated and described in support of continuous improvement of the practices and teachers formation in the distance mode.